Clavulanate combinations with mecillinam, cefixime or cefpodoxime against ESBL-producing Enterobacterales frequently associated with blaOXA-1 in a paediatric population with febrile urinary tract infections. (28th August 2021) - Birgy, André; Madhi, Fouad; Jung, Camille; Levy, Corinne; Cointe, Aurélie; Bidet, Philippe; Hobson, Claire Amaris; Bechet, Stéphane; Sobral, Elsa; Vuthien, Hoang; Ferroni, Agnès; Aberrane, Saïd; et al.
Abstract: Objectives: Oral treatment of febrile urinary tract infections (FUTIs) can be impaired by MDR Enterobacterales often combining ESBL and inhibitor-resistant genes. We studied the impact of β-lactamases and Enterobacterales' genotypes on the cefixime, cefpodoxime and mecillinam ± amoxicillin/clavulanate MICs. Materials and methods: In this multicentric study, we included 251 previously whole-genome-sequenced ESBL-producing Enterobacterales, isolated in French children with FUTIs. The MICs of cefixime, cefpodoxime, mecillinam alone and combined with amoxicillin/clavulanate were determined and analysed with respect to genomic data. We focused especially on the isolates' ST and their type of β-lactamases. Clinical outcomes of patients who received cefixime + amoxicillin/clavulanate were also analysed. Results: All isolates were cefixime and cefpodoxime resistant. Disparities depending on bla CTX-M variants were observed for cefixime. The addition of amoxicillin/clavulanate restored susceptibility for cefixime and cefpodoxime in 97.2% (MIC50/90 of 0.38/0.75 mg/L) and 55.4% (MIC50/90 of 1/2 mg/L) of isolates, respectively, whatever the ST, the bla CTX-M variants or the association with inhibitor-resistant β-lactamases (34.2%). All isolates were susceptible to mecillinam + amoxicillin/clavulanate with MIC50/90 of 0.19/0.25 mg/L, respectively. Neither therapeutic failure nor any subsequent positive control urine culture were reported for patients who received cefixime + amoxicillin/clavulanate as an oral relay therapy ( n  =   54). Conclusions: Despite the frequent association of ESBL genes with inhibitor-resistant β-lactamases, the cefixime + amoxicillin/clavulanate MICs remain low. The in vivo efficacy of this combination was satisfying even when first-line treatment was ineffective. Considering the MIC distributions and pharmacokinetic parameters, mecillinam + amoxicillin/clavulanate should also be an alternative to consider when treating FUTIs in children.